Combination of platelet rich fibrin and carbonate hydroxyapatite alloplastic bone graft as periodontal tissue engineering in management of chronic periodontitis: a case report - Arni I. Djais; Nurfaisah Nurfaisah (Journal of Dentomaxillofacial Science, 2020)
Objective:Chronic periodontitis lesions include loss of attachment and bone and are regarded as irreversible. Conventional procedures cannot restore the periodontal tissue to its original form. Periodontal tissue engineering is regenerativemedicine novel therapy by either implanting biomaterials. Platelet Rich Fibrin (PRF) as second generation platelet and Carbonate Hydroxyapatite (CHA) alloplastic bone graft can be used in surgical therapy because ease, inexpensive method and does not need any addition of exogenous compounds and a second surgical site and procedure. This case report aims to evaluate the clinical and radiographic effectiveness combination of both for the treatment of chronic periodontitis.Methods:A 21-year-old female was reported with chief complaint tooth mobility. Initial examination revealed grade two mobility ofÂ  35 with 9 mm distobuccal and distolingual pocket depth. The Periapical radiograph revealed a large diffused periapical radiolucency in relation to 35. Periodontal surgery was done and the osseous defect was filled with CHA bone graft and PRF.Results:There was a significant change in pocket depth and grade of mobility six months after surgery to 3 mm and grade one mobility.Radiographs showed resolution of an osseous defect.Conclusion:It was concluded that combined PRF with CHA bone graft can be used to treat chronic periodontitis as simple technique periodontal tissue engineering.